The Effect Of Work Engagement And Income Satisfaction To The Work Competence Of Employees With Satisfaction Work As An Intervening Variable In The Office Binjai City Regional Secretariat - Andi Affandi; Kiki Farida Ferine (International Journal of Society and Law, 2024)
The aim of this research is to determine and analyze the influence of Job Involvement and Income Satisfaction on Job Competence which is mediated by Job Satisfaction at the Binjai City Regional Secretariat Office. This research was carried out at the Binjai City Regional Secretariat Office. The type of research is associative quantitative. The sample in this study was 24 employees with ASN and honorary status in the General Section of the Binjai City Regional Secretariat Office. The sampling technique in this research uses a saturated sample, where the entire population will be sampled in this research, 24 people. The research results show that Job Involvement has a significant influence on Job Competence as shown by the T-Statistic value of 10,633 > 1.96 and the P Value of 0.000 < 0.05. On the influence of Income Satisfaction on employee work competence, the T-Statistic data obtained was 6,260 > 1.96 and the P-Value value was 0.000 < 0.05 or there was an influence of Income Satisfaction on Work Competence. Work Engagement has a significant effect on Employee Job Satisfaction with a T-Statistic value of 15,172 > 1.96 with a P-Value value of 0.001 < 0.05. Income satisfaction has a significant effect on employee job satisfaction. This can be seen from the results of the T-Statistic value of 9,523 > 1.96 with a P-Value value of 0.000 < 0.05. On the influence of Job Satisfaction on Job Competence, the T-Statistic value is 1,060 < 1.96 with a P-Value of 0.290 > 0.05, which means that Job Satisfaction has no significant effect on the Job Competence of the Binjai City Regional Secretariat Office. In the indirect effect, the results show that Job Satisfaction has a role as an intervention variable in explaining the relationship between Income Satisfaction and Job Competence. This shows that improvements in Income Satisfaction can increase Job Satisfaction, which ultimately contributes to increasing Work Competence at the Binjai City Regional Secretariat Office.